Theoretical Advances in MBenes for Hydrogen Evolution Electrocatalysis - Yanwei Wang; Qi Jia; Ge Gao; Ying Zhang; Lei Zhang; Shun Lu; Ling Fang (Energies)
Two-dimensional transition metal borides (MBenes) have emerged as promising electrocatalysts for hydrogen evolution reactions (HERs), attracting significant research interest due to theoretical computations that enhance the understanding and optimization of their performance. This review begins with a comprehensive summary of HER mechanisms, followed by an in-depth examination of the geometric and electronic properties of MBenes. Subsequently, this review explores MBene-based electrocatalysts for HERs, employing free-energy diagrams and an electronic structure analysis to assess both the intrinsic catalytic activity of MBenes and the theoretical performance of single-atom modified MBenes. Finally, the prospects and challenges associated with MBenes are discussed, providing valuable insights to guide future research in this area. Overall, this topic holds significant relevance for researchers in the HER field, and this review aims to deliver theoretical insights for the optimal design of advanced MBene electrocatalysts.